Activation of the stress protein response inhibits the STAT1 signalling pathway and iNOS function in alveolar macrophages: role of Hsp90 and Hsp70. Issue 4 (13th April 2010) - Howard, Marybeth; Roux, Jérémie; Lee, Hyon; Miyazawa, Byron; Lee, Jae-Woo; Gartland, Brandi; Howard, Amanda J; Matthay, Michael A; Carles, Michel; Pittet, Jean-François
Abstract : Background and aim: Alveolar fluid clearance is impaired by inducible nitric oxide synthase (iNOS)/nitric oxide (NO)-dependent mechanisms in acute lung injury (ALI)/acute respiratory distress syndrome (ARDS). The activation of the stress protein response (SPR) in alveolar macrophages on iNOS-dependent NO production in response to interferon γ (IFNγ), a major cytokine present in the airspace of patients with ALI, was investigated. Methods: The SPR was activated in murine and primary human alveolar macrophages prior to analysis of signal transducer and activator of transcription factor 1 (STAT1) activation, iNOS mRNA and protein synthesis, and NO production. Results: SPR activation resulted in inhibition of IFNγ-mediated NO production (p=0.001) with >95% detergent insolubilisation of the STAT1 protein. Its subsequent proteasomal degradation was partially reversed with pretreatment of cells with the chemical chaperone glycerol. This early effect of the SPR was caused by the complete disruption of heat shock protein 90 (Hsp90)–STAT1 binding, as shown by immunoprecipitation. Recovery of STAT1 activation and recovery of iNOS synthesis occurred within 12 h after SPR activation (p=0.02). NO production (as compared with non-SPR controls) did not occur until 48 h later (p=0.02). SPR-induced Hsp70 (Hsp70i) expression caused a late inhibition of NO production (p=0.02). Inhibiting >50% Hsp70i expression recovered NO production to control levels whereas overexpressing Hsp70i in the absence of the SPR inhibited NO production (p=0.02). Conclusion: Early inhibition of STAT1 following its dissociation from Hsp90, and later inhibition of iNOS activity by Hsp70i, represent novel mechanisms by which SPR activation modulates the IFNγ signalling in alveolar macrophages. These results highlight a potential clinical application for Hsp90 inhibitors in modulating NO signalling during the early phase of acute lung injury.